FEATURES OF BIOCHEMICAL MARKERS OF RAT BLOOD SERUM CAUSED BY MODELING OF PEROXIDATIVE PERIODONTITIS, ALIMENTARY PROTEIN DEFICIENCY BY MEANS OF A THERAPEUTIC AND PROPHYLACTIC COMPLEX - Hurtova, Y.M.; Shnaider, S.A.; Dienha, O.V.; Klenovska, S.V.; Yakimenko, D.O.; Rachynskyi, S.V.; Blazhkiv, N.O. (World of Medicine and Biology, 2025)
The study was devoted to the researching of the effect of the therapeutic and prophylactic complex on the blood serum biochemical markers in rats with peroxidative periodontitis and protein deficiency. The experiment involved 30 male Wistar rats divided into three groups: intact, a group with combined pathology and a group with combined pathology, which received the therapeutic and prophylactic complex. After 60 days, total bilirubin, total cholesterol, total protein and elastase activity were quantified in serum. Combined pathology elevated bilirubin, depleted total protein and increased elastase activity versus controls, confirming hepatobiliary stress, hypoproteinaemia and inflammation. Therapeutic and prophylactic complex normalised bilirubin, restored protein and reduced elastase compared with untreated pathology, while lowering cholesterol beneath intact values. The data highlight the hepatoprotective, protein-sparing, lipid-modulating and anti-inflammatory potential of the complex.